Syntactic transfer in the initial stages of adult third language and fourth language acquisition - Tavakol, Mahbube; Jabbari, Aliakbar (Indonesian Journal of Applied Linguistics, 2016)
This paper elucidates the articulated proposals for the initial stages of adult third language (L3) syntactic transfer, addressing their application for L3 and the subsequent fourth language (L4) acquisition. The study was set to demonstrate empirical evidence in line with or against the tenets of the models and to indicate if and how syntactic transfer might obtain differently depending on the language being acquired– L3 vs. L4. The models to be tested were Full Transfer/Full Access (FT/FA), L2 Status Factor Hypothesis (LSFH), Cumulative Enhancement Model (CEM) and Typological Primacy Model (TPM). Following a principles and parameters framework, six parameters were selected to generate several language pairings and an adult female’s L3 Italian and L4 German’s early spontaneous productions of the selected features were audio-recorded. The accuracy levels with which the features were produced in tandem with the results of error analyses violated the positions of FT/FA as considered for L3/s acquisition and CEM and consistently identified Typological proximity and L2 status as affecting syntactic transfer during the early stages multilingual acquisition.